DESIGN OF PATIENT MEDICAL RECORD FILE TRACER INFORMATION SYSTEM WITH WATERFALL METHOD - Agnia, Fadilatul; Syahidin, Yuda; Elvira, Shinta (Jurnal Teknik Informatika (Jutif), 2024)
Tracer is essential since it serves as a barrier and substitute for medical record files when they come from the storage rack. Tracer Helps locate medical record files if they are not on the storage shelf and shows where the storage shelf is when the file is saved again. The problem that arises from Hospital X in Bandung area is that it has not implemented the use of Tracer during the procedure of retrieving medical record files and the procedure of searching for files when files are needed only relying on expedition books. The purpose of this study is to prevent and reduce misfiles and dropouts of file for medical record and simplify the procedure of tracking file for medical record. Descriptive qualitative research methods are applied to the design of its system. Data is gathered through interviews and observation. Waterfall method for system development. Microsoft Visual Studio 2010 and Microsoft Access as the coding process and database and produces medical record file tracer card output. The software functions flawlessly, and every menu can be accessed.